Gender pay gap: A macro perspective - Akiko Terada Hagiwara; Shiela F. Camingue-Romance; Joseph E. Zveglich (Asian Development Bank (ADB), 2018)
This paper examines the factors influencing the gender wage gap by using an unbalanced crosscountry aggregated panel data set for a sample covering 53 economies for the period 1995-2010. Using robust estimators proposed by Lewbel (2012) to correct for heterogeneity and endogeneity, results suggest that a higher female share in the industry sector tends to widen the gender wage gap regardless of a country's development stage. While having more children widens the gender wage gap, as expected, the effect is only statistically significant for developing countries. In developed countries, more labor force participation by women seems to narrow the gender wage gap, probably due to the number of female labor market entrants taking up higher-paying service sector jobs. For developing countries, closing the gender gaps in labor force participation and education is not sufficient to achieve gender wage parity. Higher-paying jobs should be created by developing the service sector in these economies.
Keywords: E24; J16; J31; 330; developing countries; gender; instrumental variables; panel data; wage gap